Identification and verification of a novel epigenetic-related gene signature for predicting the prognosis of hepatocellular carcinoma - Wang, Chenchen; Yao, Chengye; Sun, Yan; Chen, Jiayi; Ge, Yangyang; Wang, Yu; Wang, Fuquan; Wang, Li; Lin, Yun; Yao, Shanglong (Frontiers in Genetics, 2022)
Hepatocellular Carcinoma (HCC) is a common malignant tumor with a poor prognosis. Epigenetic dysregulation is now considered to be related to hepatocarcinogenesis. However, it is unclear how Epigenetic-Related Genes (ERGS) contribute to the prognosis of HCC. In this study, we used the TCGA database to identify prognostic ERGS that were differentially expressed in HCC patients. Then, using Least Absolute Shrinkage and Selection Operator (LASSO) regression analysis, a 6-gene signature was constructed and patients were divided into high and low-risk groups. Validation was performed on HCC patients from the ICGC database. Patients in the high-risk group had a significantly lower chance of survival than those in the low-risk group (p < 0.001 in both databases). The predictive ability of the signature was determined by the Receiver Operating Characteristic (ROC) curve. The risk score was then shown to be an independent prognostic factor for Overall Survival (OS) of HCC patients based on the results of univariate and multivariate analysis. We also created a practical nomogram combining the prognostic model with other clinical features. Moreover, functional enrichment analysis revealed that these genes are linked to tumor immunity. In conclusion, our findings showed that a novel 6-gene signature related to epigenetics can accurately predict the occurrence and prognosis of HCC.